2012
DOI: 10.1007/s13197-012-0785-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth promoting effects of some lichen metabolites on probiotic bacteria

Abstract: In the present study, the extract of four natural lichen species Canoparmelia eruptens, Everniastrum cirrhatum, Parmotrema austrosinense and Rimelia cetrata were studied for the source of natural antioxidant and their purified secondary metabolites were evaluated for growth promoting effects on probiotic bacteria Lactobacillus casei. The methanolic fraction of lichen species showed moderate to high antioxidant activity in the order P. austrosinense > E. cirrhatum > C. eruptens > R. cetrata. The lichen metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Structures for more than 1050 dif fe rent lichen substances have been reported to date (Mol nar & Farkas 2010, StockerWorgotter 2008. The li chen substances and li chen extracts exert a remarkable va rie ty of biological effects; antibacterial, antiviral, antifungal, an ti pro tozoal, antiherbi vore, antimutagenic, antioxidant, an ti tu mor, an ti ulcerogenic, antinociceptive, antipyretic, antiinflammatory, antiprolifer ative and cytotoxic effects, car dio vascular protective, gluco sidase inhibitory and probiotic sti mu lating activities (Muller 2001, Behera et al 2005a,b, 2012, Ran ko vic 2007, Verma et al 2011, Mahadik et al 2011, Manojlovic et al 2012, Gaikwad et al 2014. Des pite of these manifold activities of lichen metabolites been re cognized, their therapeutic poten tial has not yet been fully ex plo red and thus remains pharma ceutically unexploited (Cri t tenden & Porter 1991).…”
Section: Anti-lipoxygenase Radical Scavenging and Antimicrobial Actimentioning
confidence: 99%
“…Structures for more than 1050 dif fe rent lichen substances have been reported to date (Mol nar & Farkas 2010, StockerWorgotter 2008. The li chen substances and li chen extracts exert a remarkable va rie ty of biological effects; antibacterial, antiviral, antifungal, an ti pro tozoal, antiherbi vore, antimutagenic, antioxidant, an ti tu mor, an ti ulcerogenic, antinociceptive, antipyretic, antiinflammatory, antiprolifer ative and cytotoxic effects, car dio vascular protective, gluco sidase inhibitory and probiotic sti mu lating activities (Muller 2001, Behera et al 2005a,b, 2012, Ran ko vic 2007, Verma et al 2011, Mahadik et al 2011, Manojlovic et al 2012, Gaikwad et al 2014. Des pite of these manifold activities of lichen metabolites been re cognized, their therapeutic poten tial has not yet been fully ex plo red and thus remains pharma ceutically unexploited (Cri t tenden & Porter 1991).…”
Section: Anti-lipoxygenase Radical Scavenging and Antimicrobial Actimentioning
confidence: 99%
“…Currently, 1050 secondary metabolites are known which are unique to lichens (Stocker-Worgotter, 2008; Verma & Behera, 2015). Bioactivity studies on lichen metabolites reported in recent years indicate their therapeutic potential in terms of natural antioxidants, antimicrobial, anticancer, probiotic, anti-angiogenic, and cardiovascular protective agents Gaikwad et al, 2014;Koparal et al, 2010;Mahadik et al, 2011;Srivastava et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Higher quantities of usnic acid in the thallus would be expected if protection of the photobiont from excess UV light is a main function (Armaleo et al 2008;McEvoy et al 2006). Consalazinic acid, along with salazinic acid and atranorin, have been shown to possess antioxidant activities (Gaikwad et al 2012). The greater presence of consalazinic acid in the thallus may help mitigate oxidative stress caused by the photosynthetic activity of green algae in the thallus, which is the first partner to be damaged by oxidative stress (Kong et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The major CBSM produced by A. centrifuga are alectoronic acid, atranorin and usnic acid; X. cumberlandia produces stictic, norstictic and usnic acids; and X. viriduloumbrina produces usnic, consalazinic and salazinic acids. Usnic acid and atranorin are thought to have light screening properties (Armaleo et al 2008;BeGora & Fahselt 2001;McEvoy et al 2006;Solhaug et al 2009Solhaug et al , 2010, the stictic acid complex is thought to have antiherbivory properties (Asplund et al 2009;Gauslaa 2005;Lawrey 1980) and the salazinic acid complex is thought to have antioxidant properties (Gaikwad et al 2012). These three species of lichens colonize the rock surface and overlap in their distributions (Brodo et al 2001;Hale 1990;Lendemer 2005;Thomson 1984), exhibiting different life history strategies (Deduke et al in press).…”
Section: ¤ ¤ ¤mentioning
confidence: 99%